"Pariwisata Inklusi: Potensi Pasar Kreneng Denpasar sebagai Destinasi Wisata yang Aksesibel dan Inklusif" - Dewi, I Gusti Ayu Melistyari; Aprinica, Ni Putu Isha (Journal of Hospitality Accommodation Management (JHAM), 2024)
This research study aims to explore and uncover the potential of Kreneng Market in Denpasar City as an accessible and inclusive tourist destination. The objective is to identify the challenges and opportunities in enhancing accessibility and creating an inclusive tourism experience for all visitors, including those with special needs. The study adopts a qualitative approach, utilizing interviews, observations, and document analysis to gather data. The findings reveal several challenges faced by Kreneng Market, such as limited physical accessibility, lack of easily accessible information, and communication barriers for visitors with special needs. Additionally, factors such as lack of awareness and understanding of the needs of visitors with special needs, inadequate training for market staff and vendors, and barriers in policy implementation hinder the progress of creating an inclusive tourism environment. Despite these challenges, the research also highlights the efforts made by market management, local government, and other stakeholders in improving accessibility and inclusive tourism. These efforts include physical improvements, staff and vendor training programs, awareness campaigns, and collaboration with the local community. The transformation of Kreneng Market into a tourist attraction has shown positive outcomes in terms of improved accessibility and inclusive tourism experience. This research study aims to explore and uncover the potential of Kreneng Market in Denpasar City as an accessible and inclusive tourist destination. The objective is to identify the challenges and opportunities in enhancing accessibility and creating an inclusive tourism experience for all visitors, including those with special needs. The study adopts a qualitative approach, utilizing interviews, observations, and document analysis to gather data. The findings reveal several challenges faced by Kreneng Market, such as limited physical accessibility, lack of easily accessible information, and communication barriers for visitors with special needs. Additionally, factors such as lack of awareness and understanding of the needs of visitors with special needs, inadequate training for market staff and vendors, and barriers in policy implementation hinder the progress of creating an inclusive tourism environment. Despite these challenges, the research also highlights the efforts made by market management, local government, and other stakeholders in improving accessibility and inclusive tourism. These efforts include physical improvements, staff and vendor training programs, awareness campaigns, and collaboration with the local community. The transformation of Kreneng Market into a tourist attraction has shown positive outcomes in terms of improved accessibility and inclusive tourism experience.